Bioactive Potential of Endophytic Fungi Isolated from Eucalyptus Globulus - Yadav, Sunny (My University, 2023)
This study aimed to isolate and characterize antimicrobial compounds from Eucalyptus globulus, a widely known medicinal plant with potential therapeutic properties. The plant material was collected, dried, and subjected to solvent extraction using a non-polar organic solvent ethyl acetate. The crude extract obtained was then fractionated using column chromatography, and the resulting fractions were tested for their antimicrobial activities. The bioactive fraction was further purified using various chromatographic techniques, such as thin- layer chromatography (TLC)and Column chromatography. A total of 8 fraction from extract ES1 and 13 fraction from extract ES2 were obtained. Pooling of fraction on the basis of TLC was performed. The antimicrobial of the isolated compounds was evaluated against a panel of clinically relevant bacterial strains using standard antimicrobial assays. The results revealed potent inhibitory effects of the isolated compounds against both Gram-positive and Gram-negative bacteria. The characterization of the isolated compounds using phytochemical analysis confirmed their chemical structures and provided valuable insights into their properties. The identified compounds belong to different chemical classes, such as terpenoids, phenolics, or alkaloids, known for their antimicrobial properties. These findings highlight the potential of Eucalyptus globulus as a valuable source of bioactive compounds with significant antimicrobial activities. In conclusion, in this study we successfully isolated and characterized antimicrobial compounds from Eucalyptus globulus. The identified compounds exhibited promising activities against a range of bacterial pathogens. Further studies are warranted to elucidate the mechanisms of action and potential therapeutic applications of these compounds, with the ultimate goal of developing novel antimicrobial agents for clinical use.
Keywords: Endophytic fungi; Bioactivity; Antimicrobial; Antioxidant